2007
DOI: 10.2174/138920207780368187
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Genomics of Glucose Transporters

Abstract: Glucose is the major energy source for mammalian cells as well as an important substrate for protein and lipid synthesis. Mammalian cells take up glucose from extracellular fluid into the cell through two families of structurallyrelated glucose transporters. The facilitative glucose transporter family (solute carriers SLC2A, protein symbol GLUT) mediates a bidirectional and energy-independent process of glucose transport in most tissues and cells, while the Na + /glucose cotransporter family (solute carriers S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
411
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(431 citation statements)
references
References 180 publications
(209 reference statements)
12
411
2
6
Order By: Relevance
“…An earlier study indicates that Cytochalasin B, a promiscuous small-molecule ligand that binds to and blocks glucose transport through the Slc2a family of glucose transporters (19), blocks ribose salvage in cultured mammalian cells (20). The best-studied hepatic Slc2a transporter is Slc2a2 (also known as GLUT2) (21). In agreement with previous reports (22), we found that Slc2a2 mRNA levels are enriched in the liver, kidneys, and intestines (Fig.…”
Section: Significancesupporting
confidence: 92%
See 1 more Smart Citation
“…An earlier study indicates that Cytochalasin B, a promiscuous small-molecule ligand that binds to and blocks glucose transport through the Slc2a family of glucose transporters (19), blocks ribose salvage in cultured mammalian cells (20). The best-studied hepatic Slc2a transporter is Slc2a2 (also known as GLUT2) (21). In agreement with previous reports (22), we found that Slc2a2 mRNA levels are enriched in the liver, kidneys, and intestines (Fig.…”
Section: Significancesupporting
confidence: 92%
“…Hepatic phenotypes of patients with Fanconi-Bickel syndrome include hepatomegaly and enhanced glycogen accumulation (48). Slc2a2 is a high-capacity glucose transporter (21), and many phenotypes found in Slc2a2 KO mice and patients with Fanconi-Bickel syndrome are likely caused by altered glucose consumption. However, we show that Slc2a2 also transports ribose.…”
Section: %Id/gmentioning
confidence: 99%
“…In order to be transported into the parasite, glucose has to cross several membranes (Fig. 2); it is transported into the erythrocyte by the facilitative glucose transporter GLUT1 located in the erythrocyte plasma membrane (43) and can freely pass the parasitophorous vacuole membrane (44). Finally, glucose is transported over the parasite plasma membrane via P. falciparum hexose transporter (PfHT), the primary glucose transporter that can also transport fructose (45).…”
Section: P Falciparum Glucose Transportersmentioning
confidence: 99%
“…These residues are important for substrate recognition and sugar transport specificity (Barrett et al, 1999;McVieWylie et al, 2001;Dawson et al, 2001). Interestingly, zebrafish Glut10 does not have the PESPR motif in loop 6 present in all GLUTs, which may contribute to its low-rate saturable glucose transport activity (Dawson et al, 2001;Zhao and Keating, 2007).…”
Section: Characterization Of Slc2a10 In Zebrafishmentioning
confidence: 99%